PENGARUH COMPLAINT HANDLING TERHADAP PATIENT LOYALTY MELALUI SATISFACTION COMPLAINT HANDLING DI RUMAH SAKIT PENYELENGGARA BPJS YOGYAKARTA - Wiwik Suryandartiwi (LPPM Universitas Awal Bros, 2020)
This study aims to determine the effect of complaint handling on patient trust through Satisfaction Complaint Handling at the BPJS Yogyakarta Hospital. This type of research is a causal research using a quantitative approach. The population and samples used were 80 patients at the BPJS hospital in Yogyakarta. The internal analysis used is Partial Least Square (PLS). The findings in this study proved that Interactional Justice had a significant effect on Satisfaction Complaint Handling while Procedural Justice and Distributive Justice had no significant effect on Satisfaction Complaint Handling. Then it was also proven that Satisfaction Complaint Handling had a significant effect on Patient Loyalty.